Voidopolis - Kent, Charlotte; Saiber, Arielle (The MIT Press, 2023)
"Longlisted for the 2023 Lumen Prize, a hybrid digital artistic and literary project in the form of an augmented reality book, which retells Dante's Inferno as if it were set in pandemic-ravaged New York City. Voidopolis is a digital performance about loss and memory presented as an augmented reality (AR) book with a limited lifespan. The book loosely retells the story of Dante's Inferno as if it were the dystopic experience of wandering through New York City during the pandemic; instead of Virgil, however, the narrator is guided through this modern hellscape by a caustic hobo named Nikita. Voidopolis is meant to culminate in loss. It features images that are created by digitally "wiping" humans from stock photography and text that is generated without the letter "e"--in homage to Oulipo author Georges Perec's A Void, a 300-page novel written entirely without the letter--by using a modified GPT-2 text generator. The book, adapted from a series of Instagram posts that were ultimately deleted, is likewise designed to disappear: its garbled pages can only be deciphered with an AR app, and they decay at the same rate over a period of one year, after which the decay process restarts and begins again. At the end of this decay cycle, only the printed book, with its unintelligible pages, remains. Each July 1, the date the project first started on Instagram, the book resets again, beginning anew the cycle of its own vanishing. A first-of-its-kind augmented reality book from a major university press, Voidopolis is a unique and deeply affecting artwork that speaks as much to our existential moment as it does to the fragility of experience, reality, and our connection to one another."
Keywords: Mustatea, Kat; Dante Alighieri / 1265-1321 / Inferno / In art; Augmented reality art; Inferno (Dante Alighieri); Art; Experimental fiction; Dystopian fiction; Künstlerbuch